The Use of Problem Based Learning Model to Improve Student Learning Outcomes in Economics for 10th Grade at SMA Negeri 3 Buru Selatan - Solissa, Afrily Alvina Handayani; Manuhuttu, Silvia; Ubra, Franklin W (Universitas Pattimura, 2025)
This study examines the effectiveness of the problem-based learning (PBL) model in enhancing learning outcomes for 10th-grade students in Economics. This research utilized a quasi-experimental method with a non-equivalent control group pretest-posttest design involving two groups: an experimental class employing PBL and a control class applying conventional learning methods. The research instruments included pre-tests, post-tests, observation sheets, and questionnaires to measure students' responses toward PBL. Findings indicated that the post-test average in the experimental class showed a significantly higher improvement than the control class. The N-Gain value for the experimental class was classified as high, indicating a positive impact of PBL on students' understanding. Furthermore, the observation sheets and questionnaires revealed that students were more actively engaged, felt motivated, and demonstrated better collaborative and critical thinking skills. Overall, the PBL model proved effective in enhancing students' learning outcomes